A cost analysis of a minimum pension guarantee for the individual pension system in Turkey - Sule Sahin; Adem Yavuz Elveren (The University of Utah, Department of Economics, 2009)
The returns from individual accounts in pension schemes are subject to fluctuations in capital markets. This increases income uncertainty for the beneficiary and exposes individuals to the risk of fluctuations in the economy in general, and of the stock market in particular. This fact has recently gotten considerable attention from policymakers. A minimum pension guarantee is a way to avoid this pitfall by providing a minimum annuity regardless of the actual investment performance of individual accounts. In this study, we present a cost analysis of a minimum benefit guarantee mechanism for the Individual Pension System in Turkey, a privately managed defined contribution scheme which was introduced in 2003 as a complement to the traditional pay-as-you-go system. We examine the cost estimates and the probability of guaranteed payoffs under various economic and demographic assumptions.
Keywords: 330; defined contribution; individual pension system; pension guarantees; Turkey